Effect of Addition of Tertiary-Butyl Hydroquinone into Palm Oil to Reduce Wear and Friction Using Four-Ball Tribotester - Norzahir, Sapawe; Syahrullail, Samion; Zulhanafi, P.; Nor Azwadi, C.S.; Muhammad Farhan, Hanafi (Taylor & Francis Group, 2016)
Replacing mineral oil with vegetable oils as lubricants continues to attract interest, due to their environmentally-friendly characteristics and ease of disposal. However, one disadvantage can be low thermal-oxidative stability. The purpose of our research is to investigate ways in which oxidation can be contained by combining palm oil with a phenolic antioxidant. A homogeneous mix of palm oil and tertiary-butyl-hydroquinone was found to exhibit satisfactory antioxidant properties and reduce wear and friction. Superior mineral engine oil was used to benchmark the performance.